Decoding Myth and Ideology: A Semiotic Study of Smartphone Advertisements - Km Tri Sutrisna Agustia; Ni Luh Sutjiati Beratha; I Wayan Pastika; I Nyoman Udayana (Interdisciplinary Social Studies, 2024)
Smartphones are becoming more ingrained in daily life, and the way they are marketed on platforms like YouTube will continue to shape societal attitudes toward technology, progress, and consumerism. This study explores the formation of myths and ideologies in smartphone advertisements from YouTube, utilizing semiotic analysis as its primary framework. The study focuses on two specific smartphone ads from YouTube: the Oppo Reno 12 campaign titled "Unbox The Future," and the Vivo Y28 campaign emphasizing "Endless Battery Life." The study utilizes Barthes' levels of meaning, along with insights from Eco and Lakoff, to reveal the ways in which smartphone advertisements construct and propagate narratives of progress, innovation, and technological superiority, all while embedding these messages within broader ideological and cultural implications of digital marketing in shaping consumer perceptions and behaviours. It calls for further investigation into the long-term cultural impacts of these advertising strategies and their role in reinforcing or challenging existing social norms and values in our increasingly digitized world. In doing so, this study not only contributes to the field of semiotics but also provides a critical lens through which we can examine the cultural power of digital advertising.